TEKNOLOGI INFORMASI, PROFESIONALISME ACCOUNT REPRESENTATIVE DAN APLIKASI E-TAX TERHADAP PENERIMAAN PAJAK - Lely Suryani (Universitas Pamulang, 2019)
Research on the effect of information technology, account representative professionalism and e-tax applications on tax revenue in the Pratama Tax Office in Kebayoran Baru Tiga. The sampling method and the use of primary data through random sampling. multiple linear regression is used in analyzing data. Each variable uses the validity test and reliability test so that the r count> r table and the Cronbach Alpha value> 0.60. The results of the normality test obtained 0.121. Partially, information technology has no effect on tax revenues, while account representative professionalism is positive, there is a significant and significant effect on tax revenue. Simultaneously, information technology and professionalism of account representatives have a positive and significant influence on tax revenue with fcount> ftabel.